Trend analysis and forecast of pre‐monsoon rainfall over India. (April 2016) - Narayanan, Priya; Sarkar, Sumana; Basistha, Ashoke; Sachdeva, Kamna
Abstract : Pre‐monsoon (March, April and May ‐ MAM) rainfall over India is highly variable. A pre‐whitened Mann‐Kendall test was used to investigate trends in rainfall during MAM. The results indicate the presence of a significant (at the 10% level) increasing trend at four stations (Ajmer, Bikaner, Indore and Kolkata), out of which two stations (Ajmer and Bikaner) show a statistically significant increasing trend. A decreasing trend is observed at two stations (Belgaum and Minicoy). Practical significance was also explored in terms of percentage changes, using the Theil‐Sen median slope estimator. Forecasts made using a univariate autoregressive integrated moving average (ARIMA) model for MAM indicate that there has been a significant rise in the pre‐monsoon rainfall over the northwestern part of India.